Nucleic acid-triggered catalytic drug release - Ma, Zhaochun (The National Academy of Sciences, 2000)
We propose a concept for the rational design and synthesis of highly selective chemotherapeutic agents that makes direct use of genetic information about the disease state. The key idea is to use the mRNA or DNA specific to the disease state to trigger the catalytic release of a cytotoxic drug by promoting the association of a prodrug with a catalyst capable of releasing the drug. We demonstrate the feasibility of such an approach in vitro with a model system that is based on the hydrolysis of p-nitrophenyl esters by imidazole. In our model system, the catalytic component consists of an imidazole group linked to the 5′ end of a 15-mer that is complementary to the 5′ end of the triggering oligodeoxynucleotide. The corresponding prodrug component consists of a p-nitrophenol ester linked to the 3′ end of an 8-mer oligodeoxynucleotide that is complementary to the 3′ end of the triggering sequence. We show that this system efficiently releases p-nitrophenol in the presence of all three components and that the reaction is catalytic and undergoes multiple turnovers. We also show that the complex between the catalytic component and the triggering oligodeoxynucleotide behaves like an enzyme and follows Michaelis–Menten kinetics, with a K(M) of 22 μM and a k(cat) of 0.018 min(−1). Most importantly, we show that catalytic release of p-nitrophenol is sensitive to the presence of a single base-pair mismatch.